“Gosto de descobrir minhas próprias verdades”: uma análise sobre a identidade irreligiosa de agnósticos e ateus em Imperatriz-MA - SILVA, Tiago Vasconcelos (2021)
The historical decline of Catholicism, as a predominant religion in Brazil, has been observed by sociologists in recent years, especially considering the data obtained from the 2000 and 2010 census surveys. In contrast, and in accordance with secularizing assumptions rooted in the idea of modernity, the relative growth of those who declare themselves “without religion” stands out for the same analysis. Such changes in the religious scenario, in a way, expose a crisis of institutional belonging and disenchantment. In this sense, the present dissertation aims to carry out a sociological study regarding the irreligious identities of certain self-declared agnostic and/or atheistic social actors. To this end, a qualitative research was carried out, where content analysis of the interviews was performed, obtained with some students and teachers from higher education institutions in the city of Imperatriz, MA, in order to better understand the formation of these identities, starting from their narratives. From this micro perspective, a context of fragmented identities was observed, as well as the transition from a religious to a secularized moral, characterized by the constant questioning of dogmas, especially those spread by the Judeo-Christian tradition.